The Influence of Employee Engagement, Employee Communication, Transformational Leadership, and NLP Learning on Sustainable Human Resource Management with Mediation of Employee Performance - Lisna Nurpida; Nera Marinda Machdar; Hadita; Zahara Tussoleha Rony (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study aims to examine the effects of employee engagement, employee communication, attitude, transformational leadership, and Neuro-Linguistic Programming (NLP) Learning on Sustainable Human Resource Management (Sustainable HRM), with employee performance serving as a mediating variable. This research employs a quantitative approach using a survey method. The research population consists of managerial-level employees (leaders to managers) from companies in West Java who participated in training programs conducted by Job Training Institute (LPK) “X”. A total of 360 respondents were selected using purposive sampling. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that employee engagement, employee communication, transformational leadership, and NLP Learning have a positive and significant effect on employee performance, while attitude does not have a significant effect on employee performance. Furthermore, employee performance is found to have a positive and significant effect on Sustainable HRM. Mediation analysis reveals that employee performance partially mediates the relationship between employee engagement, transformational leadership, and NLP Learning and Sustainable HRM. However, employee performance does not significantly mediate the effects of employee communication and attitude on Sustainable HRM. These findings highlight that the achievement of Sustainable HRM is not solely determined by individual and organizational practices directly, but is strongly influenced by the organization’s ability to enhance employee performance as a key mediating mechanism. This study contributes theoretically by reinforcing the role of employee performance as a mediator in the Sustainable HRM framework and by introducing NLP Learning as a relevant human resource development approach in the Indonesian organizational context. Practically, the findings provide insights for organizations and job training institutions in designing performance-oriented and sustainability-driven human resource development strategies.